2021
DOI: 10.1111/ijfs.15273
|View full text |Cite
|
Sign up to set email alerts
|

Evolutions of rheology, microstructure and starch hydrolysis of pumpkin‐enriched bread during simulated gastrointestinal digestion

Abstract: In this study, the influences of pumpkin flour additions to breadmaking on evolutions of microstructure, rheology and starch hydrolysis during simulated gastrointestinal digestion were investigated. Compared to white bread (PB0), the bread supplemented with 20% pumpkin flour (PB20) showed more continuous and fibrous gel network structure with most starch granules encapsulated in the network throughout the in vitro digestion. Due to the dilution of digestive fluids and enzymatic hydrolysis, the digesta moduli a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The G″ of control emulsions remained dominant (G″ > G′) during the initial, gastric and small intestinal phases, exhibiting fluid‐like behaviour (Fig. 5a) (Iqbal et al ., 2019; Ge, Iqbal, et al ., 2021; Ge, Wu, et al ., 2021). G′ remained dominant at low applied frequency ranges in NAM emulsion digesta (≈0.1–0.6 rad s −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The G″ of control emulsions remained dominant (G″ > G′) during the initial, gastric and small intestinal phases, exhibiting fluid‐like behaviour (Fig. 5a) (Iqbal et al ., 2019; Ge, Iqbal, et al ., 2021; Ge, Wu, et al ., 2021). G′ remained dominant at low applied frequency ranges in NAM emulsion digesta (≈0.1–0.6 rad s −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Optical and confocal microscopy were used to investigate the microstructure and the location of water droplets throughout the oil phase before and after GIT digestion. For optical microstructures, an Olympus CX‐31, Olympus Optical Co., Ltd., Japan, with a 40× objective lens was utilised to examine the microstructures of Control, NAM and HAM emulsions before and within the simulated GIT digestion (oral, gastric and small intestinal phases) (Ge, Iqbal, et al ., 2021; Ge, Wu, et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ge et al . (2021) reported that the addition of different amounts of pumpkin powder, rich in dietary fibre and bioactive compounds, reduced bread‐specific volumes and originated more compact structures which encapsulated starch granules, retarding starch digestion. Moreover, gluten‐free breads with more compact structure showed reduced in vitro glycaemic responses (De La Hera et al ., 2014; Carini et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%